Characterizations of wet mercury deposition on a remote high-elevation site in the southeastern Tibetan Plateau. (November 2015) - Huang, Jie; Kang, Shichang; Zhang, Qianggong; Guo, Junming; Sillanpää, Mika; Wang, Yongjie; Sun, Shiwei; Sun, Xuejun; Tripathee, Lekhendra
Abstract: Accurate measurements of wet mercury (Hg) deposition are critically important for the assessment of ecological responses to pollutant loading. The Hg in wet deposition was measured over a 3-year period in the southeastern Tibetan Plateau. The volume-weighted mean (VWM) total Hg (HgT ) concentration was somewhat lower than those reported in other regions of the Tibetan Plateau, but the VWM methyl-Hg concentration and deposition flux were among the highest globally reported values. The VWM HgT concentration was higher in non-monsoon season than in monsoon season, and wet HgT deposition was dominated by the precipitation amount rather than the scavenging of atmospheric Hg by precipitation. The dominant Hg species in precipitation was mainly in the form of dissolved Hg, which indicates the pivotal role of reactive gaseous Hg within-cloud scavenging to wet Hg deposition. Moreover, an increasing trend in precipitation Hg concentrations was synchronous with the recent economic development in South Asia. Highlights: The lowest HgT concentration in precipitation was found at Southeast Tibet Station. MeHg concentration and wet deposition flux were among the highest at our study site. HgD dominated the concentration and flux of HgT in wet Hg deposition. A long-term increasing trend in the HgT concentration was found at our study site. Abstract : An increasing trend in the precipitation Hg concentrations was synchronous with the recent economic development in South Asia.